Slow Information Diffusion and the Inertial Behavior of Durable Consumption. Issue 5 (1st October 2015) - Luo, Yulei; Nie, Jun; Young, Eric R.
Abstract: This paper studies the aggregate dynamics of durable and nondurable consumption under slow information diffusion (SID) due to noisy observations and learning within the permanent income hypothesis framework. We show that SID can significantly improve the model's predictions on the joint behavior of income, durable consumption, and nondurable consumption at the aggregate level. Specifically, we find that SID can significantly improve the model's predictions for: (i) smoothness in durable and nondurable consumption, (ii) autocorrelation of durable consumption, and (iii) contemporaneous correlation between durable and nondurable consumption.